WANPRESTASI KONTRAK SEWA USAHA CUCIAN MOBIL/MOTOR ANTARA PERUSAHAAN DAERAH BIMEX DENGAN PENYEWA DI KOTA BENGKULU - Natasya Basanida Sirait; Maryati Bachtiar; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Lease is an agreement, whereby one party binds itself to provide enjoyment of an item to another party for a certain period of time, with payment of a price agreed by that party. For those who rent out, the rights and obligations are to obtain payment in exchange for services and deliver the rental goods to the lessee. While the rights and obligations of the lessee are to obtain the use of the leased goods and to pay the rent periodically. If the rights and obligations of each party are not fulfilled, it can be called default. The agreement will terminate if the rights and obligations of the lessor and the lessee have been carried out in accordance with the agreement.The location of this research is the Regional Company Bimex Bengkulu. This study aims to identify and analyze the implementation of a car/motorcycle laundry rental contract between a Bimex Bengkulu Regional Company and a tenant in the city of Bengkulu and to find out the form of settlement of a car/motorcycle laundry rental contract default between a Bimex Regional Company and a tenant in the city of Bengkulu.This research is an empirical juridical research, the population is Bimex Regional Companies and tenants, the samples are Director of General Affairs and Finance of Bimex Regional Companies, Head of General Division of Bimex Regional Companies and tenants. Sources of data in this study are primary, secondary, and tertiary data. The data collection techniques used were library research, interviews, and documentation. The analysis carried out is an analysis of a qualitative approach.Based on the results of this study the authors concluded that at the time of execution of the contract the lessee did not carry out his obligations in accordance with the contract. The tenant always breaks his promise and also does not become a good head of household so that by not implementing an honest and proper attitude, it causes losses for the Bimex Regional Company.Keywords: Contract, Lease, Default